2004
DOI: 10.1007/s00015-004-1112-4
|View full text |Cite
|
Sign up to set email alerts
|

Plio-Pleistocene folding in the southern Rhinegraben recorded by the evolution of the drainage network (Sundgau area; northwestern Switzerland and France)

Abstract: The southern Rhinegraben represents a key area to unravel the Neogene paleohydrographic history of the northern Alpine foreland. At least, three successive main drainage systems are documented by the youngest sediments of the graben fill. They are respectively pre-, syn-and post-dating the folding of the Jura Mountains (about 10-5 Ma ago).Pliocene to recent uplift and shortening of the Pliocene fluvial gravel ("Sundgauschotter"), which accumulated on a nearly plain surface, and the progressive deflection and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 23 publications
4
46
0
Order By: Relevance
“…Vertical uplift rates may also be estimated along the Florimont and Réchésy anticlines, where the fold amplitude is in the order of 150 m. Within the given time frame, this yields a minimum uplift rate that is also in the order of 0.05 mm/a. This estimate is in agreement with uplift rates that were deduced from the amount of uplift of Pleistocene alluvial terraces along the Largue, Ill and Thalbach Rhine tributaries, where they traverse anticline crests traceable in the Sundgau gravels (Giamboni et al 2004b). …”
Section: Tj Urgsupporting
confidence: 89%
See 1 more Smart Citation
“…Vertical uplift rates may also be estimated along the Florimont and Réchésy anticlines, where the fold amplitude is in the order of 150 m. Within the given time frame, this yields a minimum uplift rate that is also in the order of 0.05 mm/a. This estimate is in agreement with uplift rates that were deduced from the amount of uplift of Pleistocene alluvial terraces along the Largue, Ill and Thalbach Rhine tributaries, where they traverse anticline crests traceable in the Sundgau gravels (Giamboni et al 2004b). …”
Section: Tj Urgsupporting
confidence: 89%
“…The eastern end of the Sundgau gravel sheet W of Basel is clearly erosional. Previous authors attributed the southward shift of the water divide either to a slow-down (or end) of upwarping of the Vosges-Black Forest arch , or alternatively, to accelerated subsidence in the northern URG and a concomitant drop of the local base level, causing subsequent regressive erosion in the southern URG (Doebl 1970;Schumacher 2002;Giamboni et al 2004b). Our own data (Ustaszewski & Schmid 2006 and this work) hint towards a third possible explanation, namely that both abandonment of the Sundgau riverbed and subsequent reorganisation of the drainage system were triggered by shortening-induced neotectonic uplift.…”
Section: Geomorphologic and Geological Field Evidence For Latest Pliomentioning
confidence: 99%
“…The gravels rest with an erosional unconformity on Mesozoic and/or Tertiary strata (Liniger 1967). In the Sundgau area the SFC gravel sheet reaches a thickness of 30 m (Giamboni et al 2004b), while in the Forêt de Chaux thicknesses of up to 65 m are reported (Chauve et al 1979). Sedimentological features of the SFC Gravels imply that they were deposited by a low-gradient braided river system characterised by low sinuosity shifting channels (Giamboni et al 2004b).…”
Section: Drainage System Evolution and Geomorphic Settingmentioning
confidence: 99%
“…The fault-related folds along the Chailluz Thrust, the Avant-Monts Fault and along the Lomont, Bisontin and Quingey Faisceaux form distinct ridges. The modern drainage pattern of the region is roughly parallel to the ENE-WSW striking structural trend and has undergone a complex Neogene evolution that was controlled by tectonic and climatic events (Liniger 1966;Petit et al 1996;Giamboni et al 2004b;Berger et al 2005;Ziegler and Fraefel 2009). …”
Section: Drainage System Evolution and Geomorphic Settingmentioning
confidence: 99%
See 1 more Smart Citation